INTEGRASI KONSELING KESEHATAN REPRODUKSI DAN DAKWAH: PERSPEKTIF ORGANISASI PRODUKSI - Harahap, Fatma Sylvana Dewi (JURNAL AT-TURAS, 2014)
This research will analyze dynamics integration counseling health reproduction as aplikation science and religion in level epistemological, acsiological, and ontologic. Therefore, teori pros cons science and religion, historis of islamic about science, islamic education about science and religion, monotheism and science, modern science and rule dialectics of Hegel and reactualization tradition of ilmiah islamic will be explained for support concept counseling health of reproduction and propaganda through production organic in media practis. Through production organic approach that processed with step pra production, production and have production and distribution to marketing for “capture” audiens until be customers found comprehension that juvenile can be consument fixed industri media practis that can bring positve effect as well as negatif effect to lifestyle one of them keep health of reproduction. Counseling health of reproduction contain propaganda is one of step aplicatif integration science and religion as curve deterrence to negative effect media practis to health of reproduction. Because generation that health one of them form affection a people woment.